Ground water regimes containing country rock minerals in Southern Kuzbass (case study: Narysk-Ostashkin); IOP Conference Series: Earth and Environmental Science; Vol. 33 : Contemporary Issues of Hydrogeology, Engineering Geology and Hydrogeoecology in Eurasia - Domrocheva E. (Hydrogeochemistry, 2016)
Title screen